Non-performing loans and bank efficiency of conventional and Islamic banks in OIC countries - Setiawan, Chandra (2012)
Banks are one of the an important sources of financing in most developing countries as other sources of financing (i.e stocks and bond markets) are relatively less developed to cater for the financing required for economic growth. For example, if we were to look into the GCC (the cooperation council for the Arab States of the Gulf) countries: Bahrain, Kuwait, Oman, Saudi Arabia, and United Arab Emirates ) the amount of domestic credit provided by banking sector (% of Gross Domestic Product) ranges from 36 to 88 percent in the periods from 1995 to 2005 (WDI, World Bank). This is common among most developing countries globally where banks play a dominant role (more than 70% of the financing on average) in the financial system. This applies to both the conventional banks and the Islamic banking sector that is growing competitively in these countries. Therefore, to discharge their responsibilities effectively, the banking sector must be cost, profit and revenue efficient. Furthermore it has to have an effective mechanism to avoid adverse selection and minimize the amount of non-performing loans (NPL) for the conventional banks and nonperforming financing (NPF) for the Islamic banks. This will consequently help the banking sector to perform better and contribute towards the nation’s economic growth. This thesis addresses the issue of the relationship between efficiency and NPL/NPF of conventional and Islamic banks and the determinants of the NPL and NPF. Despite the numerous evidences documented so far mainly on the efficiency of conventional banks, but there is no comprehensive evidence on the inter-temporal relationships between efficiencies and NPL/NPF of conventional and Islamic banks in OIC countries. The Data Envelopment Analysis (DEA) approach is used to measure cost, revenue and profit efficiencies of conventional and Islamic banks for the period of 1993 – 2007 for OIC countries (denoted as Middle-East region and Turkey in this study), the Asian, and African. Overall, the results on efficiencies show that cost efficiency of conventional banks outperform their Islamic banking counterparts for the regions selected: Asian, African, Middle East and Turkey. However, no significant differences were observed for profit efficiency of Islamic banks and profit efficiency of conventional banks in the Asian and the Middle East region and Turkey. The efficiency time lines show that the cost efficiency behavior is more stable over the sample period in the different regions and years and dominates the revenue and profit efficiency. Alongside, the efficiency time lines show that the financial crisis in 1997-1998 had affected both the conventional and Islamic banks. Overall, both banking streams have an opportunity to further improve their cost, revenue and profit efficiency. An analysis on the determinants of cost, revenue and profit efficiencies revealed that the cost efficiency of both banking streams in all regions is more affected by the internal determinants (bank-specific variables) than the external factors (macroeconomic variables). This is due to the fact that cost is under the control of the management and they have the prerogative to manage cost in the best way possible. The revenue efficiency of conventional banks and Islamic banks for total sample is affected by internal variables. However, revenue efficiency of conventional banks is more sensitive to external variables compared to their Islamic banks counterparts. The profit efficiency of conventional banks is more affected by internal variables compared to external variables compared to profit efficiency of Islamic banks in the total sample. The results on the determinants of NPL/NPF of conventional and Islamic banks support the view that both bank-specific and macroeconomic variables determine the level of NPL/NPF of conventional and Islamic banks. Therefore, investors could use these findings to examine the assets quality of banks and the Central Bank could use this information to develop a framework for measuring and assessing assets quality – an important element of study on financial stability. The management of banks should pay attention to some factors that have significant relationships with NPL/NPF for conventional and Islamic banks when providing loans/ financing in order to control the level of impaired loans/financing. The test results on the inter-temporal relation between bank efficiency (cost and profit), capital and problem loans/financing, as proposed by Berger and DeYoung (1997) support the “bad management” hypothesis for all regions for both conventional and Islamic banks, except for Asian region. This finding indicates that the internal management problem tend to precede the problem loans/financing. The result rejects the ‘bad luck’ hypothesis for conventional banks in all regions. However, the result supports ‘bad luck’ hypothesis for Islamic banks in Asian region and Middle East region and Turkey. This finding implies an increase in NPF precedes the decrease in cost efficiency of Islamic banks, problem financing of Islamic banks may be driven by uncontrollable external or exogenous factors. The ‘skimping’ behavior also supported by the findings for all regions for both Islamic and conventional banks except for both stream of banks in the African region. The findings also support the ‘moral hazard’ hypothesis for both the conventional and Islamic banks in all regions except Africa. This implies that there is a possibility that the incidence of high volume of problem loan/financing in these regions is not involuntary but rather the management trade-off decision between short-term operating costs and long-run profitability. The management might rationally decide to reduce short-term expenses by skimping resources allocated to loan origination and monitoring.